(untitled) (Jurnal Ekonomi dan Manajemen, 2023)
In the competitive freight service industry, improving employee performance is key to a company’s competitiveness. This study analyzes the influence of organizational culture, motivation, and work discipline on employee performance at Bela Belo Transindo Malang. Using a quantitative approach with multiple linear regression, this study involved 54 permanent employees. Results show that organizational culture significantly affects performance (t = 5.095; p = 0.000), as does motivation (t = 2.340; p = 0.023). However, work discipline does not significantly affect performance (t = 0.607; p = 0.547). Simultaneously, all three variables significantly impact performance (F = 38.327; p = 0.000), with a determination coefficient (R²) of 0.697. These findings indicate that organizational culture is the most dominant factor in improving employee performance. The study implies that companies should strengthen their organizational culture, enhance motivation through reward systems and a conducive work environment, and improve discipline systems to optimize overall employee performance.